Pediatric Orthopaedic Surgeon Coding Trends After Changes to the Current Procedural Terminology Evaluation and Management Coding Guidelines in 2021 - Dylan S. Koolmees, MD; Alec Kadrie, BS; Clayton C. Bettin, MD; Derek M. Kelly, MD; Benjamin W. Sheffer, MD (Elsevier, 2024)
Background: Starting in 2021, the Centers for Medicare and Medicaid Services and the American Medical Association revised the Evaluation and Management (E&M) criteria of the Current Procedural Terminology coding selection. This retrospective study determined the changes in E&M coding level for pediatric orthopaedic patients and examined the effect of the changes on percentage of work relative value units (wRVUs) from clinic and surgery. Methods: Coding levels for all outpatient visits at our institution were analyzed from 2020, January 2021, December 2021, and January 2023. The total number of pediatric orthopaedic visits were collected, tabulated under the corresponding E&M code, and expressed as a percentage of total E&M codes within the corresponding time frame. The total change in wRVU generated from the E&M coding changes was compared between the clinic and operating room by examining the total average coding and percentage of total average for each group and the overall total and total percentage change in wRVUs. Results: There was a statistically significant difference in level of coding for both established and new patients from 2020 compared with January 2021, December 2021, and January 2023. Established patients showed a large decrease in level-2 visits and a complimentary increase in level-3 visits. New patients demonstrated a statistically significant increase in level-4 visits, which was sustained at the 2-year mark. From 2020 to 2021, there was a 29% increase in percentage of wRVUs from clinic, and a 6-point increase in wRVUs from clinic compared with surgery. Conclusions: Our study found an increase in level of coding after the E&M guideline changes, especially for new patients. This finding does not indicate that there were more complex pediatric orthopaedic cases but rather the new E&M guidelines accurately captured the complexity of each visit. There was a substantial increase in wRVUs from clinics, comparing immediately before and after the guideline change, which was largely sustained at the 2-year mark. Key Concepts: (1) This study is important because it highlights specific specialty information for pediatric orthopaedic surgeons before and after the evaluation and management (E&M) guideline changes. (2) It is vital for pediatric orthopaedic surgeons to understand and appropriately apply the guidelines to each patient visit to ensure accurate coding. (3) Our study was the first to demonstrate the changes in level of coding after the E&M guidelines changed, and the effects of percent of work relative value units originating from clinic encounters. Level of Evidence: Level III, retrospective case control